SISTEM INFORMASI AKUNTANSI ASET TETAP PADA PT WYZ - Budiasningrum, Retno Setya; Yanti, Yulianan Dama; Karomah, Nurul Giswi (JURNAL LENTERA AKUNTANSI, 2023)
The accounting information system of each company has a different process flow from one to another in accordance with company policy but not out of the context of accounting science and applicable PSAK. The purpose of this study was to determine the fixed asset accounting information system, documents used, recording tangible fixed asset journals, related functions, and internal control of fixed assets. This research adopts qualitative methods with interviews, ethnography, document analysis and literature study. The results showed that the fixed asset accounting information system implemented by PT WYZ is effective considering that the fixed assets owned by the company are fairly small for now. In a healthy internal control is quite good with the existence of physical control and evaluation that is done periodically every semester. But currently there is no special application used in managing fixed assets.